Catalytic Transfer Reduction of Electron Deficient Alkenes and an Imine Using Potassium Formate and Catalytic Palladium Acetate - Bhuiyan, Md Mosharef Hossain (Biological Sciences - PJSIR, 2005)
Chemoselective reduction of a, b-unsaturated cyanostannyl esters, ketones and an imine with potassium for- mate as hydrogen donor and palladium acetate as homogeneous catalyst in DMF was observed to proceed readily with saturation of C-C and C-N double bonds, without any concomitant reduction of cyano, carboxylate, halogen or carbonyl groups and demetallation.